Multicomponent analysis of T1 relaxation in bovine articular cartilage at low magnetic fields. Issue 5 (10th December 2018) - Petrov, Oleg V.; Stapf, Siegfried
Abstract : Purpose: The multi‐exponential character of T1 relaxation in bovine articular cartilage was investigated at low magnetic fields below 0.5 T. The ultimate aim was to identify a parameter based on the T1 relaxation time distribution as a biomarker to biochemical features of osteoarthritis. Methods: Osteoarthritis conditions were simulated by enzymatic digestion of cartilage with trypsin. Fast‐field cycling NMR relaxometry was carried out in the magnetic field range B0 = 70 μT to 600 mT. The data were analyzed in terms of T1 distributions on a log‐time scale using inverse Laplace transform, whereas integral properties such as mean T1 s and distribution widths were obtained without data inversion from logarithmic moment analysis and a stretched‐exponential fit to the data. Attempts were also made to differentiate between water dynamic components through multi‐Lorentzian decomposition of average relaxation‐rate dispersions. Results: T1 distribution in bovine articular cartilage was found to be bimodal, with the dominating, long component shifting toward larger values following trypsin digestion. The effect is more prominent toward lower magnetic field strength. This shift leads to an overall increase of the distribution width and an equivalently more pronounced deviation from exponential behavior. Conclusion: The logarithmic width of T1 distribution functions at fields of 0.5 T and below, and the stretched‐exponential decay fit exponent β, show a significant trend after trypsin digestion of cartilage. These 2 parameters are suggested as possible biomarkers for osteoarthritis in humans and can be acquired entirely in vivo, with increasing significance for lower magnetic field strengths.